Inflammatory myofibroblastic tumour arising incidentally as a polypoid lesion in the gallbladder - Carlos Filipe C. Abrantes; Mário Rui Silva; Rui Caetano Oliveira; Catarina Eloy; Maria Augusta Cipriano; Lígia P. Castro (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Inflammatory myofibroblastic tumour (IMT) is a rare mesenchymal neoplasm that usually originates from abdominal soft tissues. A female patient aged 50 years presented with a 1.2 cm gallbladder polyp. The microscopic study showed spindle cell proliferation in an edematous background rich in lymphocytes and plasma cells. Immunohistochemistry showed positivity for vimentin, smooth muscle actin, and anaplastic lymphoma kinase (ALK), and negativity for other markers. Fluorescent in situ hybridization (FISH) revealed ALK gene rearrangement. The diagnosis was IMT of the gallbladder, a unique case considering that it was identified at the early stage of development of these neoplasms.